Regulation of Endoplasmic Reticulum Stress-Autophagy: A Potential Therapeutic Target for Ulcerative Colitis - Qiao, Dan; Zhang, Ziwei; Zhang, Yali; Chen, Qian; Chen, Yujun; Tang, Yingjue; Sun, Xiong; Tang, Zhipeng; Dai, Yancheng (Frontiers in Pharmacology, 2021)
Ulcerative colitis (UC) is a chronic nonspecific inflammation that mainly involves the rectum, colonic mucosa, and submucosa. A large number of studies have shown that endoplasmic reticulum stress (ERS)-induced autophagy plays an important role in the pathogenesis of UC. ERS is a homeostasis imbalance caused by misfolded or unfolded proteins aggregated in the endoplasmic reticulum (ER) cavity. And excessive ERS triggers the unfolded protein response (UPR), increase in inositol-requiring enzyme 1, and the overload of Ca2+, which activate the autophagy pathway. Autophagy is a conservative way of cellular self-degradation. Dysregulated autophagy causes inflammation, Disruption of the Intestinal Barrier, and imbalance of intestinal homeostasis, thus increasing the risk of intestinal diseases. This study reviewed the pathogenesis of ERS, UPR, and autophagy in UC, so as to provide potential new targets and more effective treatment options for UC.